Sensor innovations helping unmanned vehicles rapidly growing smarter, smaller, more autonomous and more powerful for navigation, mapping, and target sensing. Issue 1 (19th January 2015) - Bloss, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review recent developments in sensors for application in unmanned vehicles. Design/methodology/approach – This study included in-depth interviews with exhibitors of sensors and sensor integrators at trade shows and contact with providers of such devices to the industry. Findings – Sensor innovation has made giant leaps in producing much smaller and smarter sensors to address unmanned vehicle requirements. Practical implications – Developers of unmanned vehicles of all types may be surprised at the sensor innovations and new applications to which sensors are being applied in this rapidly advancing field. Originality/value – A review of some of the latest sensor innovations and applications that one might have seen if they had been on the exhibition floor at the recent trade shows, followed industrial publications or announcements from sensor developers.